Serial killers and sadistic murderers: up close and personal - Levin, Jack (Prometheus Books, 2008)
Introduction -- Conversing with the devil -- Gaining a sadistic thrill -- Silencing the lambs -- Looking more innocent than an innocent man -- Killing without a care -- Hating enough to kill -- Hiding domestic violence -- Fighting the culture of silence -- Killing for company -- Planning and plotting to kill -- Motivating mindless murder -- Teaming up to kill -- Threatening to kill -- Victimizing the vulnerable -- Stigmatizing the community -- Preventing the murderous impulse -- Responding to the murderous impulse -- Endnotes -- Index